1995
DOI: 10.1046/j.1469-0705.1995.05010055.x
|View full text |Cite
|
Sign up to set email alerts
|

Trisomy 18: first‐trimester nuchal translucency with pathological correlation

Abstract: Diagnosis of trisomy 18 was made following prenatal screening at 11 weeks' gestation for ultrasonographically detected nuchal translucency and subsequent chorionic villus sampling. An intact fetus was therapeutically aborted and pathological examination was undertaken. We conclude that, although the etiology of nuchal translucency remains unclear, it does not appear to be lymphatic or cardiac in origin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Another assumption is to relate the congestion to malformations affecting the cardiovascular system (Moscoso, 1995). We are aware of only one case report that correlates nuchal translucency in a trisomy 18 fetus with full pathological examination (Jackson et a[., 1995). No association has been reported with cardiac and lymphatic lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another assumption is to relate the congestion to malformations affecting the cardiovascular system (Moscoso, 1995). We are aware of only one case report that correlates nuchal translucency in a trisomy 18 fetus with full pathological examination (Jackson et a[., 1995). No association has been reported with cardiac and lymphatic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The jugular lymphatic obstruction sequence (Jones, 1988) is the pathological mechanism responsible in the embryonic period for secondtrimester cystic hygroma and for its residual sequelae (secondary webbing of the neck and neonatal peripheral lymphoedema). Very few data are available to explain the pathophysiology of nuchal oedema (Moscoso, 1995;Jackson et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…In 1995, shortly after the first publication on increased NT and chromosomal abnormalities38, Jackson et al were the first to consider a pathological correlation between an 11‐week fetus with trisomy 18 and ultrasonographically detected increased NT. They concluded that ‘although the etiology of increased NT remains unclear, it does not appear to be lymphatic or cardiac in origin’39. Yet, as Yves Ville indicates in his Opinion ‘Ten years on and still a pain in the neck?’40, cardiac or lymphatic origin, both or neither, the quest for the etiology of increased NT continues.…”
Section: The Heart and The Lymphatic System In The Etiology Of Increamentioning
confidence: 99%
“…Earlier pathological observations appeared to rule out both cardiac and lymphatic origins for increased NT39. While the former remains unproven, there appears to be growing evidence for the latter.…”
Section: The Heart and The Lymphatic System In The Etiology Of Increamentioning
confidence: 99%
“…While in cases of cystic hygroma obstructed lymph is considered the underlying etiology, this appears not the case in association with increased nuchal translucency. 1819 Jackson et al, 20 for example, demonstrated the striking ab-sence of endothelial lining (by immunohistochemical staining for factor Vlll-related antigen and CD34) in tissue from the back of the neck, in a fetus with trisomy 18 diagnosed following increased firsttrimester nuchal translucency. In addition to lack of precise knowledge as to the etiology of nuchal translucency, it is also unclear why in most cases (with normal or at times abnormal chromosomes) spontaneous resolution of the nuchal translucency will occur usually within 4 weeks of diagnosis.…”
Section: Physiologymentioning
confidence: 99%